Patterns of care and outcomes with the addition of chemotherapy to radiation therapy for stage I nasopharyngeal cancer. (1st February 2018) - Verma, Vivek; Ryckman, Jeffrey M.; Simone, Charles B.; Lin, Chi
Abstract: Purpose: The standard of care for stage I (T1N0) nasopharyngeal cancer (NPC) is definitive radiotherapy (RT). Given the phase III evidence supporting combined chemoradiotherapy (CRT) for stage II NPC, we investigated practice patterns and outcomes associated with administration of chemotherapy to RT alone for stage I NPC. Methods: The National Cancer Data Base (NCDB) was queried for clinical T1N0 primary NPC cases (2004–2013) receiving curative-intent RT. Patients with unknown RT/chemotherapy status were excluded, as were benign/sarcomatous histologies and receipt of pharyngectomy. Patient, tumor, and treatment parameters were extracted. Logistic regression analysis ascertained factors associated with receipt of additional chemotherapy. Kaplan–Meier analysis was used to evaluate overall survival (OS) between patients receiving RT versus CRT. Cox proportional hazards modeling determined variables associated with receipt of OS. Results: In total, 396 patients were analyzed. Chemotherapy was delivered in 147 patients (37%). On multivariate analysis, patients treated at academic/integrated centers were less likely to receive chemotherapy ( p = .008); a racial predilection was noted, as non-black/non-white patients were also less likely to receive chemotherapy ( p = .006). Respective 5-year OS in patients receiving RT alone versus CRT were 77% and 75% ( p = .428). Receipt of chemotherapy did not independently predict for greater OS ( p = .447). Conclusions: These data do not support the routine addition of chemotherapy to definitive RT for T1N0 NPC.